Perception On Motivators, Training Supports, Barriers And Challenges To Career Planning And Advancement Among Perak Pharmacist In Malaysia Civil Service - Chang, Chee Tao (2020)
The role of pharmacists began to expand over the last two decades, covering pharmaceutical care and patient counselling. This resulted in increased demand for pharmacists to meet the expanded pharmaceutical services requirements. Some studies have shown that lack of career advancement leads to job dissatisfaction and increased employee turnover rates. At present, there is no performance-based advancement pathway defined for public pharmacists. This study is designed to explore motivation, training support and challenges for career advancement among fully registered pharmacists and provisional pharmacists (FRPs and PRPs) in the Malaysian civil service. The study was conducted in two phases. The first phase of this study is in qualitative design. A semi-structured interview guide is used to conduct face-to-face interviews. All interview sessions were recorded in audio form and transcribed verbatim. The interview sessions take an average of 20 to 30 minutes. This study was conducted among the eleven pharmacists who served in hospitals. Five themes have been identified after an interview session: career planning, opinion on subject matter expert advancement pathway, motivators for better career performance, barriers to career advancement and suggestions to overcome barriers. In general, the lack of an established specialization path for pharmacists in the civil service is seen as a major barrier to their career advancement.